Inevitable Mutual Necessity on the Path to the Problems of the Future - Toshkova, Svetla (Research Papers, 2018)
The study presents the understanding of the links between economic theory, history and philosophy in the context of the contemporary development of political-economic analyses and interdisciplinary research, and relations in science. There have been sought the grounds of the interconnection and studying of the contemporary political-economic systems and their methodological grounds in the contemporary philosophical-economic researches and economic-historical realities and characteristics. An opinion is stated on the necessity of creating the theoretical foundations of a research program in the field of contemporary perceptions about the role and place of political economy in the direction of using the historical context of the development of science, the economic and historical roots of political and economic knowledge and philosophical systems, on which the economic theories have been conceptually and methodologically constructed.